2021
DOI: 10.1007/s10653-021-01076-w
|View full text |Cite
|
Sign up to set email alerts
|

Ecological risk and enrichment of potentially toxic elements in the soil and eroded sediment in an organic vineyard (Tokaj Nagy Hill, Hungary)

Abstract: Potentially toxic elements (PTEs), such as Cu, Zn, Pb, Ni, Cr, and Co, can accumulate in vineyard soils due to repeated uses of inorganic pesticides and chemical or organic fertilizers. In sloping vineyards, PTEs can also be moved by soil erosion resulting in their accumulation in low-energy zones within the landscape, adversely affecting the soil environment. Our study evaluated the ecological risk related to the pseudo-total and bioavailable PTE contents (Zn, Pb, Co, Ni, Cr, and Cu) in the soil and eroded se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…This must encourage the application of management that will reduce solute release to avoid damages in ecosystems that are sensitive to an increase in nutrients such as the wetlands and rivers. Moreover, our research also advises about the risk of delivering potentially toxic elements, such as Manaljav et al [50] found in the sloping vineyards and Pham et al [51] in Tokaj Nagy Hill, both sites in Hungary. Runoff water transports nutritive elements from soil, but they can also mobilize toxic elements [52].…”
Section: Further Researchmentioning
confidence: 70%
“…This must encourage the application of management that will reduce solute release to avoid damages in ecosystems that are sensitive to an increase in nutrients such as the wetlands and rivers. Moreover, our research also advises about the risk of delivering potentially toxic elements, such as Manaljav et al [50] found in the sloping vineyards and Pham et al [51] in Tokaj Nagy Hill, both sites in Hungary. Runoff water transports nutritive elements from soil, but they can also mobilize toxic elements [52].…”
Section: Further Researchmentioning
confidence: 70%
“…Third, topography is also a contributing factor (Korchagin et al., 2020; Pham et al., 2022). In Champagne, France, it was estimated that the applied amount of copper pesticide was about 3−5 kg/ha each time, about three to 10 times a year, which should lead to copper contents in the vineyard soil in the range of 100–1500 mg/kg.…”
Section: The Existing Situation Of Copper In Winementioning
confidence: 99%
“…The determination of the soil texture based on the plasticity index values according to Arany (Arany plasticity index) was performed in accordance with the Hungarian Standard (MSZ-08-0205, 1978) (Table 1). Briefly, this index is calculated from the amount (cm 3 ) of deionized water added to an air-dry soil sample (100 g) until reaching the upper limit of its plasticity (Pham et al 2021;. The total salt content was analyzed by a conductivity meter type Orion 3-Star (Thermo Electron Corporation) in saturated soil samples (± 10).…”
Section: Soil Analysesmentioning
confidence: 99%
“…Mostly acid soils have developed on the magmatic rock basement of the hills, but slightly alkaline soils are also found on the loess envelope of the magmatic rocks. Our previous studies investigated the enrichment and spatial distribution of PTEs in the topsoil of the vineyards in Tokaj-Hegyalja (near Tállya and Tokaj) using point samples (Manaljav et al 2021;Pham et al 2021). Meanwhile, this study focused on the accumulation patterns, and bioavailability of PTEs complemented with human health risk assessment by applying a hillslope position-based composite sampling strategy.…”
Section: Introductionmentioning
confidence: 99%